Framework gerencial de transição em operações Hospitalares - Souza, Davenilcio Luiz de (Universidade do Vale do Rio dos Sinos, 2022)
Purpose: The growing complexity in production and service systems determined the fourth industrial revolution. A new dynamic of human relations is presented in Cyber-Physical systems through digitalization. The fusion of digital technologies and the interaction in the physical, digital and biological domains based on the enabling technologies of Industry 4.0 / Health 4.0, such as genomics, wearable devices, and sensors for health monitoring that drive success in medicine. The sustainability of the care business encourages innovation in managing health operations. In this scenario, the research aims to propose a transition managerial Framework in Hospital operations. This transition means migrating from a conventional model to a dynamic model of continuous evolution where the profitable and sustainable management of the hospital operation prevails. Design/methodology/approach: A systematic literature review on Hospital Operations Management promoted awareness of the problem. Three approaches in hospital management models were classified: i) Value-based, ii) Process-based, and iii) Mixed base, a mix of the previous approaches. The research objective achievement, an artifact based on Design Science Research (DSR), is proposed. It aims to develop the Framework where it lists the process and means that provide the transition of Hospital Operations Management through the Drivers: “Continuous Improvement” supported by the Lean Six Sigma and the “Differentiation” supported by technological innovation. The Drivers are driven by the knowledge assets of multidisciplinary teams, guided by good HR and Governance practices. The Framework is formed by three dimensions “People, Technologies and Processes”, with the enabling technologies of Industry 4.0 / Health 4.0 and the development of the continuous improvement process by the Value Stream Mapping (VSM), allied to the Time-Driven Activity-Based Costing (TDABC) to implement the mapping of the costing of the clinical conditions attended in the Hospital Unit. Findings: Model of a Continuous Improvement Project, established in the proposed Framework based on the priorities of the Hospital unit. A Project conducted by multidisciplinary teams trained in the principles of Lean Six Sigma and the associated Industry 4.0 / Health 4.0 enabling technologies. The Continuous Improvement project aims to ensure Innovation in Management by the possible succession and improvement of projects conducted by the Operation Managers in the Hospital unit. The project follows the steps of VSM/TDABC mappings of the Clinical Conditions seen in the hospital unit. It aims to establish a reliable costing standard for the manager’s decision. Finally, evaluated by Experts in Hospital Operations Management, the validation of the submitted Continuous Improvement Project Model and Framework took place. Originality/value: Among the researched publications, there is no reference to transition in hospital operations management. The theme presents relevance in the healthcare industry; the academic research in this field raises the need for Innovation in management models. Complementing an Innovative Hospital Management model by the dynamics of the science of improvement is vital to boost competitive advantages, create and maintain value for everyone involved in the care process.
Keywords: Ciência da melhoria; Diferenciação pela inovação; Framework; Lean Seis Sigma; Modelo de transição em gestão hospitalar; Tecnologias habilitadoras da Indústria/ Saúde 4.0; Valor; Differentiation through Innovation; Enabling technologies for industry/health 4.0.; Hospital management transition model; Improvement science; Lean Six Sigma; Value; ACCNPQ::Engenharias::Engenharia de Produção